Short-Term Effects of a Multidisciplinary Residential Rehabilitation Program on Perceived Risks, Confidence Toward Continuous Positive Airway Pressure Treatment, and Self-Efficacy in a Sample of Individuals Affected by Obstructive Sleep Apnea Syndrome - Scarpina, Federica; Bastoni, Ilaria; Cappelli, Simone; Priano, Lorenzo; Giacomotti, Emanuela; Castelnuovo, Gianluca; Molinari, Enrico; Tovaglieri, Ilaria Maria Angela; Cornacchia, Mauro; Fanari, Paolo; Mauro, Alessandro (Frontiers in Psychology, 2021)
Continuous positive airway pressure (CPAP) therapy is the standard treatment for obstructive sleep apnea (OSA) syndrome. However, optimizing adherence to CPAP therapy of individuals remains very challenging for clinicians because of the role played by the psychological components. In this study, we verified the changes in cognitions and beliefs of individuals after a four-week multidisciplinary residential rehabilitation program targeting the adaptation to CPAP therapy for OSA syndrome. We assessed the components of perceived risks, confidence toward the treatment, and self-efficacy through the self-report questionnaire, namely the Self-Efficacy Measure for Sleep Apnea (SEMSA) questionnaire. We also explored the role played by the temperamental traits on the changes registered in these components after the treatment. Forty-five participants completed the rehabilitation program, showing a higher level of adherence to the treatment. Significant changes were observed in terms of confidence toward the treatment, although no change was reported in terms of perceived risks and self-efficacy. Moreover, those individuals with a higher persistent temperamental trait reported a significant improvement in perceived risks, in the absence of other significant results. After the rehabilitation treatment, our participants were more prone to consider the effect of CPAP treatment on health outcomes. This was in line with the educational aim of the rehabilitation treatment. The temperament seemed to play only a marginal role in the global changes reported by our participants. We discussed the need for behavioral interventions, in addition to education, in improving self-efficacy.